Recent Advances in Mouth Dissolving Films: Formulation Strategies, Evaluation and Therapeutic Applications - C. Pandian; Gowtham A; Gunaseelan M; Pooja B; Praveen Kumar D; Keerthana M; Dhanusiya V (International Journal of Pharmaceutical Sciences and Medicine, 2026)
Mouth dissolving films (MDFs) or oral dissolving films, are a novel and convenient method for drug delivery. They become even more useful by enhancing patient compliance and instant release of the drug. When thin and flexible polymer films come in contact with saliva, they break apart and release the drug without the aid of water. MDFs are particularly beneficial for patients who cannot swallow traditional dose forms, such as bedridden patients, those suffering from dysphagia, the elderly and children1. The production of MDFs requires selecting the appropriate film forming polymers and combining them with plasticizers, sweeteners, saliva inducing agents, surfactants and active pharmaceutical ingredients (APIs) to obtain the desired mechanical strength, disintegrating time and drug release. Several techniques have been developed for the production of MDFs, such as solvent casting method, semi solid casting method, hot melt extrusion method, solid dispersion extrusion method and rolling methods2. MDFs have been used for a large number of therapeutic applications demonstrating the versatility of this novel drug delivery system. The bioavailability and dosage flexibility of the films has been enhanced by the use of nanoparticle and nano emulsion films, 3D printing of oral films and adhesion technologies, in addition to intelligent medicine and formulation technologies. The application of these techniques has extended the range of MDFs to the treatment of disorders of the central nervous system (CNS), allergic reactions, pain, control of vomiting and smoking cessation. The studies and examples of commercial oral films have proven the industrial and clinical applications of this dosage form.